Ruído e vibração incidentes ao operador de um quadriciclo agrícola - Araújo, Karla Lúcia Batista (2018)
Concern about increased production, increased time and labor shortages, other factors such as improved working conditions have been taken into account, making agricultural activities safer, healthier and more comfortable for the operator. The prototype of the agricultural quadricycle was developed to work as a smaller tractor designed to meet the characteristics present in the family agriculture, destined to smaller areas and being able to emphasize the reduction of the physical effort of the worker, when compared with the human and animal traction. The experiment was carried out in the experimental area belonging to the agricultural accident investigation laboratory LIMA, at the Department of Agricultural Engineering (DENA), Federal University of Ceará -UFC. For the accomplishment of the experiment was used an agricultural quadricycle, of the brand GERAGRI, model GE-02.Measurements of operator occupational exposure to full body and hand and arm vibrations were performed using a Delta OHM HD 2030 vibration analyzer and the guidelines followed were those determined by NHO -09 and NHO -10, and Annex A of standard NBR ISO 5008: 2015 (ABNT, 2015).In the noise analysis, a personal noise dosimeter of the brand Instrutherm, model DOS-600 was used. For full body vibration, it is concluded that with the increase of the gait, from the first to the second, there is the increase of the average accelerations in the three axes. The maximum values of the resulting vibration acceleration do not differ statistically for the hood factor in the Z axis. All present statistical difference as a function of the gait increase when analyzing the values of aren and RVVR. For the evaluation of hand and arm vibration, it was concluded that the maximum peak values in the X, Y and Z axes presented significant differences for rotation and gait, not differing for the bonnet factor. The mean values of aren are well above the limit of exposure, presenting values of up to 50 m.s-2, it is believed that these values occurred as a result of the steering wheel being located near the motor of the agricultural quadricycle. For both types of vibration evaluated, corrective measures must be taken to reduce the vibration incident to the operator, either in the hand and arm system or in the whole body. The level of noise level measured on the agricultural quadricycle near the operator's ear was high in all variables tested. It is recommended that ear protectors be used for agricultural quadricycle operators and field assistants when working with these variants used.